2012
DOI: 10.15230/scsk.2012.38.4.297
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Effect and Tyrosinase Inhibitory Activity of Lindera obtusiloba Blume Extracts

Abstract: 3+-EDTA/ H2O2 계에서 생성된 활성산소종에 대한 세 분획의 소거활성(총항산화능)은 대표적인 항산화제인 L-ascorbic acid와 비슷한 것으로 나타났다. Rose-bengal로 증감된 Abstract: In this study, the antioxidative effects and inhibitory activities on tyrosinase of Lindera obtusiloba Blume (L. obtusiloba Blume) extracts were investigated. 50 % ethanol extract, ethyl acetate and aglycone fractions of L. obtusiloba Blume were used in experiments. The DPPH (1,1-diphenyl-2-picrylhydrazyl) scavenging activities of ethyl acetate fraction of L. obtusiloba Blume was higher than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…α-arbutin is usually produced by transglucylation of hydroquinone by microbial glycosyltransferase (Zhu X et al, 2018) [23]. Studies have indicated that arbutin can prevent tyrosinase activity, thereby preventing melanin production and reducing skin pigmentation (Won et al, 2012;Chunhakant and Chaicharoenpong, 2019;Ye et al, 2019;Zhang et al, 2022) [24][25][26][27]. Recent studies have shown that α-Arbutin shows potential anti-photoaging effects, likely linked to diminished cellular inflammation from IL-6 and TNF-α (Hazman Ö et al, 2021;Lee et al, 2012) [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…α-arbutin is usually produced by transglucylation of hydroquinone by microbial glycosyltransferase (Zhu X et al, 2018) [23]. Studies have indicated that arbutin can prevent tyrosinase activity, thereby preventing melanin production and reducing skin pigmentation (Won et al, 2012;Chunhakant and Chaicharoenpong, 2019;Ye et al, 2019;Zhang et al, 2022) [24][25][26][27]. Recent studies have shown that α-Arbutin shows potential anti-photoaging effects, likely linked to diminished cellular inflammation from IL-6 and TNF-α (Hazman Ö et al, 2021;Lee et al, 2012) [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…L. obtusiloba has been used as herbal medicine for improving blood circulation and treating inflammation [ 33 ]. Previous studies demonstrated that the extract of L. obtusiloba has potent anti-oxidative and anti-inflammatory activities on atopic dermatitis and anti-allergic responses in mast cells [ 33 , 34 , 35 , 36 ]. In detail, L. obtusiloba has effects such as anti-inflammation and anti-allergy through the suppression of histamines and Th2 cytokines in a DFE/DNCB-induced atopic dermatitis model [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In detail, L. obtusiloba has effects such as anti-inflammation and anti-allergy through the suppression of histamines and Th2 cytokines in a DFE/DNCB-induced atopic dermatitis model [ 34 ]. On the other hand, L. obtusiloba inhibited ROS generation in the Fe 3+ -EDTA/H 2 O 2 system, and has potent 2,2-diphenyl-1-picryl hydrazyl (DPPH) radical scavenging activity [ 35 ]. Although many studies have reported the anti-oxidant and anti-inflammatory properties of L. obtusiloba , its protective effects of allergic asthma have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…생강나무를 이용한 국내연구는 gas chromatography mass spectrometry를 이용한 계절에 따른 생강나무의 부위별 향기 성 분 비교 분석 (Hwang et al, 2005), 제조방법에 따른 생강나무 잎 차의 성분변화 (Hwang et al, 2003), 제조방법에 다른 생강나무 잎차의 향기 성분의 변화 (Hwang et al, 2005), 잎과 가지의 정유 성분 (Kwon et al, 2007) 등이 있으며, 기능성 식품 및 화장품 소 재로서의 연구로는 식중독균에 대한 항균 활성 (Kim et al, 2014), 암 전이 억제 효과 (Yun et al, 2012), 항산화 효과 및 티로시나 아제 저해 활성 (Won et al, 2012), 광노화에 의한 주름형성 억제 효과 (Park et al, 2009), 잎 및 가지 추출물의 생리 활성 (Hong, 2013), 알레르기성 염증반응 억제 효과 (Kim et al, 2009), 항산화 활성과 미백 효과 (Bang et al, 2008) To confirm the whitening effects of L. obtusiloba flower extracts, we measured tyrosinase activity in B16F10 melanoma cells. Both LWE and LEE decreased the tyrosinase activity in a dosedependent manner.…”
unclassified